A bird survey of Sungai Kangkawat research station, Imbak Canyon Conservation Area, Sabah. - Nur Nadhirah Izzaty Selamat; Mohamad Fizl Sidq Ramji; Hilda Jelembai Neilson Ilan; Ng Wen Teng; Anna Wong@Wong Yun Moi; Annabel Timothy Pianzin; Nor Atiqah Norazlimi; Nur Syamimi Makbul (Universiti Malaysia Sabah, 2021)
A bird survey was conducted at the Sungai Kangkawat Research Station (117°3′34.593″E, 5°4′29.187″N), Imbak Canyon Conservation Area (ICCA), Sabah from 5 th until 8 th October, 2018. The objective of this survey was to produce a preliminary checklist of bird species in the study area. The primary method used was mist-netting with occasional observation from vocal and visual identification. A total of 30 mistnets were deployed for 11 hours (0630-1730 hr.) for four consecutive days with a final accumulation of 1840 net/hours. Overall, 59 species comprising 23 families were recorded throughout the survey. Of these, 114 individuals were netted representing 41 species from 13 families. The most abundant species caught was the Little Spiderhunter Arachnothera longirostra with 26 individuals. Additionally, 18 species from 10 different families were identified via opportunistic sighting and vocalisation. This includes one Critically Endangered (Helmeted Hornbill, Buceros vigil), three Vulnerable (i.e., Rhinoceros Hornbill Buceros rhinoceros, Large-billed Blue Flycatcher Cyornis caerulatus and Blue-headed Pitta Pitta baudii and 20 other Near-threatened species. Four endemic species were recorded namely the Bornean Blue Flycatcher Cyornis superbus, White-crowned Shama Copsychus stricklandi, Black-headed Pitta Pitta ussheri and Blue-headed Pitta Pitta baudii. We expect higher diversity of birds in ICCA because the species accumulation curve did not reach an asymptote until the last day of sampling. This suggests additional trapping effort with point counts along predetermined transects should be considered for future surveys.